Connecting the Dots Between Sustainable Diets and Biocultural Systems in a Rural Indigenous Community of the Ecuadorian Andes (OR20-07-19). (13th June 2019) - Gallegos, Carlos Andres; Waters, William; Carrasco, Amaya; Pintag, Mabel; Caranqui, Martha; RIofrío, Antonio; Caranqui, Joaquín; Chapnick, Melissa; Iannotti, Lora
Abstract: Objectives: Characterize the psychosocial and agroecological dimensions of sustainable diets and their roles in an Andean biocultural system. Methods: A participatory mixed-methods design: 1) focus groups ( n = 39) and key informant interviews ( n = 7) were recorded, translated, transcribed, and analyzed using three-staged coding; 2) information was triangulated with participant observations, local records, and descriptive statistics from a survey to female household heads ( n = 57); 3) rural appraisal activities for agronomic calendars and yields; 4) ten sites, purposively selected, prospected with local informants to obtain a Margelef-Shannon's K Diversity Index; 5) a subset of five sites for agroecological parameters with MO-Dirt methods for soil health and laboratory analysis; 6) a crossover analysis of agrobiodiversity, land-family size ratios and diet; and 7) four community-based system dynamics sessions to elucidate causal-loop diagrams. Results: A psychosocial dimension was centered in indigenous identity, customary institutions, and agrarian knowledge. Identity was grounded in Mother Earth ( Pachamama ) and traditional foods. Customary institutions reinforce trust and reciprocity, mobilize labor-intensive tasks and food production and processing. Traditional knowledge includes agrarian calendars, pest control, seed selection, and soil restoration measures. An agroecological dimension is characterized by a pre-Hispanic system of terraces, trenches, and contention walls, as well as ecological richness. Combined analysis of both dimensions, including ethnographic testimonials, archeological research, and local records, reveal that the community is a remarkable biocultural space, which seems to promote sustainable crop yields through the generations. Conclusions: This study suggests the viability of a reinforcement loop in indigenous-based agri-food systems, in which sustainable diets support a stable biocultural space and where the dynamic interaction between psychosocial and agroecological factors assure the stability of biocultural space. Research on biocultural systems represents an opportunity to elucidate ideas for present and future sustainability and food security challenges. Funding Sources: Funded by the Brown School's International Dissertation Award.